The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s12034-014-0059-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gamma ray attenuation coefficients of Al-4% Cu/B4C metal matrix composites at 662, 1173 and 1332 keV

Abstract: Gamma ray attenuation coefficients of metal matrix composites have been investigated. For this purpose, the linear attenuation coefficients of composites containing boron carbide (B 4 C) at different rates have been measured using a gamma spectrometer that contains a NaI(Tl) detector and MCA at 662, 1173 and 1332 keV, which are obtained from 137 Cs and 60 Co sources. The measured results were compared with the calculation obtained using computer code of XCOM for 1 keV-1 GeV gamma energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…Furthermore, they are similar to the values reported for B4C Al metal matrix composites [7] at a gamma energy level of 661.7 keV. However, the linear attenuation coefficients of Al2O3.TiO2;mm and Al2O3.TiO2;nm are lower than those of Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10] The best HVL value of 3.57 cm obtained in this study is better than the results of [9], but significantly less than the values reported for some stainless and boron steels [8].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, they are similar to the values reported for B4C Al metal matrix composites [7] at a gamma energy level of 661.7 keV. However, the linear attenuation coefficients of Al2O3.TiO2;mm and Al2O3.TiO2;nm are lower than those of Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10] The best HVL value of 3.57 cm obtained in this study is better than the results of [9], but significantly less than the values reported for some stainless and boron steels [8].…”
Section: Resultssupporting
confidence: 86%
“…The linear attenuation coefficients of Al2O3;mm and Al2O3;nm are similar to those of TiB2-reinforced B4C-silicon carbide composites [5] and spark plasmasintered B4C-Al [9]; however, they are higher than the values reported for h-BN and h-BN-TİB2 composites [4] and lower than those of Al-4% Cu/B4C metal matrix composites [6], B4C Al metal matrix composites [7], and some stainless and BSs steels [8] at 661.7 keV. At gamma energies of 1173.2 and 1332.5 keV, Al2O3;mm and Al2O3;nm samples have lower linear attenuation coefficients than Al-4% Cu/B4C metal matrix composites [6] and TiB2-reinforced B4C-SiC [10].…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations